Regiodivergent iodocyclizations for the highly diastereoselective synthesis of syn- and anti-hydroxyl-isochromanones and -isobenzofuranones: concise synthesis of the isochromanone core of the ajudazols - Thiede, Sebastian; Winterscheid, Peter Maria; Kleint, Jan F.; Schnakenburg, Gregor; Essig, Sebastian; Menche, Dirk (Synthesis, 2016)
An efficient synthetic strategy to access hydroxyl-isochromanone and -isobenzofurans from readily available joint alkene precursors by a regiodivergent one-pot iodocyclization-substitution tandem process is reported. The cyclizations proceed with excellent diastereoselectivities, with E-alkenes giving syn-configured products and Z-alkenes giving anti-products. A strong influence of light on the regioselectivity of the reaction was observed. High yields were also observed under radical conditions. The protective-group-free method enables a highly concise synthesis of the authentic isochromanone core of the ajudazols, which are highly potent inhibitors of the mitochondrial respiratory chain.
Published online: 29.12.2015
Gesehen am 27.05.2020